„Jak stać się lustrem tej nowoczesności?” Planetarność, periodyzacja i nowe studia modernistyczne - Chinitz, David (Poznańskie Studia Polonistyczne. Seria Literacka, 2014)
The main task of this article is to enter into discussion with a concept of modernism as an expressive dimension of modernity by Susan Stanford Friedman. In place of statements of epistemological nature, the author of the article proposes ontological questions and return to an understanding of modernism which would primarily stress a specific historical, global modernity. This kind of a historically motivated definition should protect the coherence of modernism as a research subject.